PENGARUH PENDIDIKAN KESEHATAN DENGAN PENDEKATAN MODELLING TERHADAP PENGETAHUAN IBU DALAM MENSTIMULASI TUMBUH KEMBANG BAYI 0-6 BULAN DI POSYANDU WILAYAH KERJA PUSKESMAS TOMALOU KOTA TIDORE KEPULAUAN - Yusuf, Yuli; Rompas, Sefti; Babakal, Abram (JURNAL KEPERAWATAN, 2016)
Abstract.Health education is a process to connects the gap of health information and health practices, which motivates a person to obtain information and be able to keep themselves become healthier by avoiding bad habits.Modeling is a person's ability to improve attention, retention, reproduction and motivation during the learning process.Knowledge of mothers on infant growth stimulation on 0-6 months can reduce errors and improve care for mothers in positive growth. Ignorance of mother about the infant growth stimulation on 0-6 months can impact on maternal difficulty to understand the importance of stimulating growth and development of infants on 0-6 months. The purpose of this Research was to determine the influence of health education with mother's modeling approach to knowledge in stimulating the growth and development of infants at 0-6 months. This Research methods uses a pre-experimental design using the design of one group pre-post test. Sampling technique is purposive sampling with a sample size of 99 people, using Wilcoxon test, at the significance level of 95% (á 0.05). Results of statistical test p value = 0.000 á <0.05. Conclusion of this research are significant health education approach to knowledge modeling mother in stimulating the growth and development of infants at 0-6 months in Integrated Service Post in The Working Area at Tomalou Public Health Center of Tidore Islans. Advice the importance of health education with modeling approaches to mothers about infant growth stimulation on 0-6 months in order to be applied at home. Keywords :Health education, Modelling, Knowledge of mothers, infant growth stimulation on 0-6 months. Abstrak.Pendidikan Kesehatan adalah proses yang menjembatani kesenjangan informasi kesehatan dan praktek kesehatan, yang memotivasi seseorang memperoleh informasi dan dapat menjaga dirinya menjadi lebih sehat dengan menghindari kebiasaan buruk. Modellingadalah kemampuan seseorang untuk meningkatan atensi, retensi, reproduksi dan motivasi selama proses belajar berlangsung.Pengetahuan ibu tentang stimulasi tumbuh kembang bayi 0-6 bulandapatmengurangi kesalahan ibudalam merawat dan meningkatkan tumbuh kembang yang positif.Ketidaktahuan ibu tentang stimulasi tumbuh kembang bayi 0-6 bulan dapat mengakibatkan ibu sulit memahami pentingnya stimulasi tumbuh kembang bayi 0-6 bulan.Tujuan penelitian ini untuk mengetahui pengaruh pendidikan kesehatan dengan pendekatan modelling terhadap pengetahuan ibu dalam menstimulasi tumbuh kembang bayi 0-6 bulan.Metode Penelitian ini menggunakan metode pra-eksperimental dengan menggunakan rancangan desain one group pre-post test.Teknik samplingyaitu purposive sampling dengan jumlah sampel sebanyak 99 orang, dilakukan menggunakan uji wilcoxon, pada tingkat kemaknaan 95% (á 0,05). Hasil Penelitian dari uji statistik yang didapatkan nilai p value=0,000 á < 0,05. Kesimpulan dari penelitian ini yaitu terdapatpengaruh pendidikan kesehatan dengan pendekatan modelling terhadap pengetahuan ibu dalam menstimulasi tumbuh kembang bayi 0-6 bulan di Posyandu Wilayah Kerja Puskesmas Tomalou Kota Tidore Kepulauan. Saran perlunya pendidikan kesehatan dengan pendekatan modelling untuk ibu tentang stimulasi tumbuh kembang bayi 0-6 bulan agar dapat diterapkan dirumah. Kata kunci:Pendidikan Kesehatan, Modelling, Pengetahuan Ibu, Stimulasi Tumbuh Kembang Bayi 0-6 Bulan.